Effects of Prenatal Hypoxia on Nervous System Development and Related Diseases - Wang, Bin; Zeng, Hongtao; Liu, Jingliu; Sun, Miao (Frontiers in Neuroscience, 2021)
The fetal origin adult diseases hypothesis was proposed by David Barker in the UK in the late 1980s, which mainly believed that adult chronic diseases originated from various adverse stimuli in early fetal development. Fetal origin adult diseases are associated with a wide range of adult chronic diseases, such as cardiovascular disease, type 2 diabetes, cancer, and neurological disorders such as depression, anxiety, and autism. Intrauterine hypoxia is one of the most common complications of obstetrics. Numerous studies have confirmed that intrauterine fetal hypoxia leads to alterations in brain structure and function and is strongly associated with neurological disorders such as cognitive impairment and anxiety. However, the mechanism that fetal hypoxia causes this adult chronic disease remains unclear. Based on the existing literature, we have summarized the causes of prenatal hypoxia, the effects of prenatal hypoxia on brain development and behavioral phenotype, the responses of different species and different periods to prenatal hypoxia, and the possible molecular mechanisms.